Evaluation of dental students’ awareness about intraoral scanners - Berrak Çakmak; Ebubekir Yıldız; Tuba Tortop (PLoS ONE, 2025)
Background There are a few studies evaluating dental students’ knowledge and awareness of intraoral scanners. This study aims to evaluate and compare the knowledge and awareness of levels 3 rd , 4 th, and 5 th -grade dental students regarding intraoral scanners and their use in orthodontics. Methods A survey adapted from similar studies was administered to a total of 278 volunteer undergraduate students [comprising 3 rd (n = 94), 4 th (n = 88), and 5 th- grade (n = 96)] to assess their awareness of intraoral scanners. Descriptive statistics, including frequencies and percentages, were used to analyze the variables within the scope of the study. The Fisher–Freeman–Halton exact test was employed to compare responses across different academic years. A p-value of <0.05 was considered statistically significant. Results Of the participants, 33.81% were 3 rd -grade, 31.65% were 4 th -grade, and 34.53% were 5 th -grade dental students. There was no significant difference in the distribution of participants across academic grades (p > 0.05). Among the students, 96.81% of the 3 rd -grade, 89.77% of the 4 th -grade, and 83.33% of the 5 th -grade students reported that they had never used an intraoral scanner (p < 0,05). A higher proportion of 3 rd -grade students (71.28%) believed that IOSs were used in the treatment of skeletal Class II malocclusions and the fabrication of maxillary expansion appliances, compared to the other grade groups. In contrast, 5 th -grade students more frequently associated IOS usage with indirect bonding procedures (63.54%) (p < 0.05). Conclusion Students in the 4 th and 5 th grades demonstrated a greater level of knowledge compared to 3 rd -grade students. It is recommended that practical training opportunities be expanded and the dental curriculum be revised accordingly to support hands-on experience with intraoral scanners.